2015
DOI: 10.1016/j.visres.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial properties of non-retinotopic reference frames in human vision

Abstract: Many visual attributes of a target stimulus are computed according to dynamic, non-retinotopic reference frames. For example, the motion trajectory of a reflector on a bicycle wheel is perceived as orbital, even though it is in fact cycloidal in retinal, as well as spatial coordinates. We cannot perceive the cycloidal motion because the linear motion of the bike is discounted for. In other words, the linear motion common to all bicycle components serves as a non-retinotopic reference frame, with respect to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Our results supported the predictions of the non-retinotopic motion- based memory hypothesis ( 5D -right). Additional results supporting this finding (with multiple vernier's inserted at multiple locations) can be found in Öğmen et al ( 2006 ), Scharnowski et al ( 2007 ), Otto et al ( 2008 ), Boi et al ( 2009 , 2011 ), and Noory et al ( 2015a , b ).…”
Section: Non-retinotopic Information Processing and Storagesupporting
confidence: 68%
See 1 more Smart Citation
“…Our results supported the predictions of the non-retinotopic motion- based memory hypothesis ( 5D -right). Additional results supporting this finding (with multiple vernier's inserted at multiple locations) can be found in Öğmen et al ( 2006 ), Scharnowski et al ( 2007 ), Otto et al ( 2008 ), Boi et al ( 2009 , 2011 ), and Noory et al ( 2015a , b ).…”
Section: Non-retinotopic Information Processing and Storagesupporting
confidence: 68%
“…The inability of the sensory memory to operate under normal viewing conditions not only challenged any role it may have in information processing, but also positioned it as a “road block” to information flow from external inputs to the rest of the modal model. However, during the last decade, evidence has been accumulating on non-retinotopic processing for various stimulus attributes such as form (Nishida, 2004 ; Öğmen et al, 2006 ; Otto et al, 2006 ; Öğmen and Herzog, 2010 ), luminance (Shimozaki et al, 1999 ), color (Nishida et al, 2007 ), size (Kawabe, 2008 ), and motion (Boi et al, 2009 ; Noory et al, 2015a ). We suggest that this non-retinotopic processing extends to sensory memory in the form of non-retinotopic sensory memory ( nr SM).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that the perceived motion of a target stimulus can be influenced by nearby motion of another object, and that this object need not be surrounding the target stimulus, as in the induced-motion paradigm (Agaoglu et al, 2015;Noory et al, 2015). In this study, we started off by replicating our previous findings that each local motion vector has a reference field associated with it, and this is manifested by increased illusory percepts of backward motion with decreasing distance to this moving reference frame.…”
Section: Discussionmentioning
confidence: 52%
“…The difference between fixation and SPEM performance in terms of a spatiotopic reference frame was not significant at stimulus encoding and VSTM stages, but it was significant for the sensory memory stage. As mentioned before, whereas earlier studies found that sensory memory uses a retinotopic reference frame, more recent studies using sequential metacontrast and Ternus-Pikler displays indicate that sensory memory can also use a motion-based nonretinotopic reference frame (Noory et al, 2015;Ogmen et al, 2006;Otto, Öğmen, & Herzog, 2006;Scharnowski, Hermens, Kammer, Öğmen, & Herzog, 2007). Because performance in sensory memory in terms of a spatiotopic reference frame was superior to that in terms of a retinotopic reference frame and because spatiotopic performance showed the typical exponential delay observed in sensory memory (see Fig.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the point lights placed on a person in the biological motion paradigm (Johansson, 1973) creates a very complex stimulus; however, by grouping these points into a meaningful Gestalt (Yantis, 1992), the visual system is capable of computing a common reference frame, which can be used to simplify the relative motions of various point lights. Several studies showed that when the stimulus allows grouping of parts, motion groupings based nonretinotopic reference frames (relative motion) account for perceived direction of motion (Agaoglu et al, 2015a(Agaoglu et al, , 2015bBoi, Öğmen, Krummenacher, Otto, & Herzog, 2009;Duncker, 1929Duncker, /1938Johansson, 1973;Noory et al, 2015). In fact, Agaoglu et al (2015b) quantified the contributions of retinotopic, spatiotopic, and relative-motion reference frames and showed that relative motion dominated both during fixation and SPEM, with a contribution more than 80% when the distance between the stimuli was 2 degrees.…”
Section: Discussionmentioning
confidence: 99%